Large scale spatial modelling of soil organic carbon dynamics - Falloon, Peter Daniel (2001)
Under the Kyoto Protocol, participating nations are required to reduce National CO₂emissions according to their 'reduction commitment' or 'quantified emissions limitation', over the first commitment period, 2008-2012. One way in which nations could achieve this would be by increasing soil carbon storage through different management practices. Most former estimates of regional scale C sequestration potential have made use of either linear regressions based on long-term experimental data, whilst some have used dynamic soil organic matter (SOM) models linked to spatial databases. Few studies have compared these two methods, and none have compared regressions with two different SOM models. This thesis presents a case study investigation of the potential of different land management practices to sequester carbon in soil in arable land, and preliminary estimates of other potential C savings.